2023
DOI: 10.1039/d2fo03701g
|View full text |Cite|
|
Sign up to set email alerts
|

Lactobacillus fermentumF40-4 ameliorates hyperuricemia by modulating the gut microbiota and alleviating inflammation in mice

Abstract: Hyperuricemia (HUA) is a systemic disease characterized by the disorder of purine metabolism and the abnormal increase of serum uric acid (UA). Probiotics can exert potential therapeutic benefits to some...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Similar studies have shown that Lacticaseibacillus rhamnosus 1155 and Limosilactobacillus fermentum 2644 can effectively reduce the levels of inflammation and oxidative damage in rats with hyperuricemia [48]. It was discovered that Lactobacillus fermentum F40-4 alleviated the level of liver and kidney damage in hyperuricemia [49]. These results suggest that ASC-1 can relieve the inflammation and oxidative stress induced by hyperuricemia.…”
Section: Asc-1 Alleviated Inflammation and Oxidative Stress In Hyperu...mentioning
confidence: 53%
“…Similar studies have shown that Lacticaseibacillus rhamnosus 1155 and Limosilactobacillus fermentum 2644 can effectively reduce the levels of inflammation and oxidative damage in rats with hyperuricemia [48]. It was discovered that Lactobacillus fermentum F40-4 alleviated the level of liver and kidney damage in hyperuricemia [49]. These results suggest that ASC-1 can relieve the inflammation and oxidative stress induced by hyperuricemia.…”
Section: Asc-1 Alleviated Inflammation and Oxidative Stress In Hyperu...mentioning
confidence: 53%
“…[31,32] Flavonoids, folate, probiotics, anthocyanins, fibers and other anti-inflammatory dietary components have been shown to reduce blood uric acid levels and improve hyperuricemia through mechanisms such as downregulating inflammatory pathways and modulating intestinal homeostasis. [15,16,[33][34][35][36][37] Further research is needed to elucidate the relationship between the inflammatory potential of food and hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…XOD inhibitors or uricases, which catalyse uric acid into a more soluble product, can prevent hyperuricemia. Cao et al [56] found in mice experiments that L. fermentum F40-4 can reduce the level of XOD and improve uric acid levels by inhibiting inflammatory responses and reshaping the gut microbiota. UA419 significantly reduced serum markers, including uric acid, XOD and inflammatory cytokines.…”
Section: New Proposals For Gout Therapy Probioticsmentioning
confidence: 99%